Developing Paper Based Diagnostic Technique to Detect Uric Acid in Urine - Islam, Md. Nazibul; Ahmed, Isteaque; Anik, Muzahidul Islam; Ferdous, Md. Sakib; Khan, Mohidus Samad (Frontiers in Chemistry, 2018)
Urinary or serum uric acid concentration is an indicator of chronic kidney condition. An increase in uric acid concentration may indicate renal dysfunction. Reliable instantaneous detection of uric acid without requiring sophisticated laboratory and analytical instrumentation such as chromatographic and spectrophotometric methods would be invaluable for patients with renal complication. This paper reports the early development of a simple, low-cost, instantaneous and user-friendly paper based diagnostic device (PAD) for the qualitative and quantitative detection of uric acid in urine. A colorimetric detection technique was developed based on the intensity of Prussian blue color formation on paper in presence of uric acid, and the reaction rate of corresponding chemical reactions on paper surface was studied. Based on the colorimetric signal produced on paper surface, a calibration curve was developed to detect unknown concentration of uric acid in urine. The effect of temperature on formation of color signal on paper surface was also analyzed. In this study, estimation of urinary uric acid using MATLAB coding on a windows platform was demonstrated as the use of software application and digital diagnostics. This paper-based technique is faster and less expensive compared to traditional detection techniques. The paper-based diagnostic can be integrated with a camera of smart phone, tablet computer or laptop and an image processing application (using windows/android/IOS platform) as a part of digital diagnostics. Therefore, with proper calibration, the paper-based technique can be compatible and economical to the sophisticated detection techniques used to detect urinary uric acid.